«Вот скажем лицом я в Китае». Стереотипы и имаготипы Китая, китайца и китайского в практике обращения к чужому в геопоэтике и геоэстетике Дмитрия Пригова - Rainer Grübel (Internationale Zeitschrift für Kulturkomparatistik)
“Let’s say, with my face I am in China”. Stereotypes and Imagotypes of China, the Chinese Man and Woman and the Chinese in the Practice of Addressing the Alien in the Geo-poetics and Geo-esthetics of Dmitrij Prigov